Des hommes d’affaires aux affaires : les entrepreneurs dauphinois et les évolutions de l’espace public (années 1730-années 1820) - Boris Deschanel (Mélanges de la Casa de Velázquez, 2022)
The aim of this contribution is to analyse the evolution of the modes of public engagement of businessmen, in the context of the French Revolution. Based on an analysis of the business community in the Dauphiné, the aim is first to evaluate this participation in political and administrative activities, and then to explain the mechanisms involved. The study will thus seek to explain the phenomenon, by combining administrative sources (particularly fiscal) and private archives. In the end, the behaviour of entrepreneurs was strongly influenced by collective dispositions and aspirations that were progressively incorporated during the 18th century, but within a deeply reshaped public space.